RANCANG BANGUN DETEKTOR SOLID STATE - Gunarwan Prayitno; Ahmad Rifai (BATAN, 2010)
Much has been charged particle detector radiation detector made by the industry, especially those engaged in the development of detection equipment and components; The d veloi>iiient and further research will be made solid state detector with silicon mat iifll. : To be able to detect charged particles (radiation), required the processing of silicon material into the detector material. The method used to make silicon detector material is a lithium evaporations. Having formed an intrinsic region contactor installation process, and with testing Telah banyak detektor pendeteksi radiasi partikel bermuatan dibuat oleh industri, khususnya yang berkecimpung da/am pengembangan peralatan dan komponen deteksi,. Perkembangan dan penelitian lebih Ian jut akan dibuat detektor solid state dengan bahan silikon. Untuk dapat mendeteksi partikel bermuatan (radiasi), diperlukan pengolahan bahan silikon menjadi bahan de,tektor. Metode yang dipakai untuk menjadikan silikon menjadi bahan detektor adalah evaporasi lithium. Setelah terbentuk daerah intrinsik dilakukan proses pemasangan kontaktor, dilanjutkan dengan pengujian.